Synthesis of choline from ethanolamine in rat brain. - Kewitz, H (1976)
Specific radioactivities of choline, acetylcholine, phosphocholine, lecithin, lysolecithin, and glycerophosphorylcholine have been measured in brain, blood, liver, and muscle after the intravenous injection of three labeled precursors: choline, methyl-labeled methionine, and ethanolamine. In relation to the specific activity of free choline in blood there was significantly more radioactivity in the free choline of brain after administration of methyl-labeled methionine and labeled ethanolamine than after labeled choline. Since the choline moiety of lipids, which returns back to the choline pool, contained less radioactivity after methyl-labeled methionine and labeled ethanolamine than after labeled choline, it is the most likely interpretation of the finding that choline, in brain can be formed by methylation of free ethanolamine. Data from liver confirm that lecithin is formed in the liver by methylation of phosphatidylethanolamine. No indication was found for the synthesis of choline in muscle. Rates of transfer and transport of choline in brain have been calculated as nmol x g-1 x min-1 as follows: turnover rate of choline, 36.5; rate of synthesis of choline by methylation and net loss of choline into the bloodstream, 6.3; inflow from the blood 6.2; outflow into the blood, 12.5; transfer into lipids and vice versa, 20; transfer to acetylcholine and vice versa, 4.